DISIPLIN SUBSIDI PERIKANAN DALAM SISTEM PERDAGANGAN GLOBAL DAN IMPLIKASINYA BAGI PERIKANAN INDONESIA - Sitanggang, Dyan F. D. (Veritas et Justitia, 2019)
Government policies providing financial aid to small and medium scale business enterprises are found everywhere around the globe, including those that is managed by Indonesia, and is allowed under the world trade arrangement managed by the WTO. An important part of this policy is subsidies made available to fishing businesses. Be that as it may, overfishing and the resulting fish stock crisis globally has made the practice of subsidizing marine fishing enterprises suspect in light of marine environment protection. This article discusses the issues of fishing subsidies as practiced in Indonesia in view of the current regime of economic law and the need to develop a sustainable fishing practices.